Systematic list, geographic distribution and ecological significance of lady beetles (Coleoptera: Coccinellidae) from the West Bank (Central Palestine) - Najajrah, Mohammad H.; Swaileh, Khalid M.; Qumsiyeh, Mazin B. (Zootaxa, 2019)
We surveyed and identified species of lady beetles from the West Bank to document their geographic distribution and understand their ecological significance. This study documents the presence of 35 species of Coccinellidae in 19 genera belonging to 10 tribes and 6 subfamilies. Seven species (mostly very rare), out of the 35 documented, are recorded for the first time in the area studied. These are Nephus (Bipunctatus) bipunctatus, N. crucifer, Scymnus (Scymnus) interruptus, S. (Parapullus) abietis, S. (Neopullus) limbatus, S. nigropictus, and S. (Pullus) suturalis. Nephus peyerimhoffi, introduced to Palestine in 1986 and later considered extirpated, is recorded from three localities in this study. The distribution of many species generally correlates with local biogeographical zones. All species recorded during the study feed on agricultural pests such as aphids and scale insects. Previously published accounts have been very limited, and while more remains to be done, this study is currently the most comprehensive in the West Bank.